Effectiveness of an Educational Program on Nursing Staffs’ Knowledge about Uses of Steroids and Their Side Effects in Al-Diwaniya Teaching hospital - Abees, Ali; Mohammed, Widad (Iraqi National Journal of Nursing Specialties, 2020)
Objective: To determine the effectiveness of the educational program on nursing staffs’ knowledge about uses of steroids and their side effects. Methodology: A pre-experimental study design (one group design: pre-test and post-test) was used. This study was conducted in Al-Diwaniya Teaching Hospital for the period from ( 28th May to 10 th June, 2020) on a non-probability (purposive) sample consisting of (30 nurses) working in Oncology unit. A questionnaire was built as a data collection tool and consisted of two parts: First part: The demographic characteristics of the nursing staff (gender, age, level of education, years of experience in hospital, participation in training courses related to nursing care for a patients undergoing to steroid therapy). Second part: It consists of two domains. The first domain contains (27) multiple-choice questions about assessment of the nursing staffs` knowledge regarding steroids and their uses, while the second domain contains (15) multiple-choice questions about assessment of the nursing staffs` knowledge regarding side effects of steroids. The validity of the questionnaire and the educational program were verified by presenting it to (14) experts. The sample has received a pre-test, educational program, and post-test. Descriptive and inferential statistics were used to analyze the results of the study using the Statistical Package of Social Sciences (SPSS) version 25 and Microsoft Excel (2010). Results: The study indicates that all the study sample responses at the pre-test were poor knowledge with a statistical mean of scores (1.20), other than the post-test, shows (100%) of the study sample have high knowledge at the mean of scores (1.91). Also, the results revealed a highly significant difference between the pre-test and post-test of the study sample after participated in the educational program at the p-value (0.0001). The conclusion of the study that the educational program was effective in the enhancement of nursing staffs` knowledge about uses of steroids and their side effects in Oncology Unit. Recommendations: The study recommended the necessity of developing continuous educational programs to educate and train nurses and all health care workers regarding steroids.